Akuntansi Kewajiban Pemerintah Perspektif KHES dan PP No. 24 Tahun 2005 tentang Standar Akuntansi Pemerintahan: Indonesia - Islamiyah, Latifatul; Faidati, Ashima (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2022)
Accounting for government obligations is regulated in government regulation (PP) number 24 of 2005 in government accounting standards statement No.09 (PSAP) concerning Liability Accounting. Liabilities are debts arising from past events, the settlement of which resulted in an outflow of government economic resources. In the context of government, obligations arise, among others, due to the use of sources of financing originating from loans. These loans can come from the public, financial institutions, other governments, or international institutions. Government obligations also occur due to engagements with employees working for the government, responsibilities to the broader community, namely benefits, compensation, compensation, allocation/reallocation of income to other entities, or obligations with other service providers. Government obligations can also arise from procuring goods and services from third parties that have yet to be paid by the government at the end of the fiscal year. In KHES Concerning, accounting for obligations has been regulated in Chapter IV concerning Accounting for KHES Liabilities, which consists of 16 articles (Articles 765 to 780).